Variable Presentations and Ablation Sites for Manifest Nodoventricular/Nodofascicular Fibers. (September 2019) - Nazer, Babak; Walters, Tomos E.; Dewland, Thomas A.; Naniwadekar, Aditi; Koruth, Jacob S.; Najeeb Osman, Mohammed; Intini, Anselma; Chen, Minglong; Biermann, Jurgen; Steinfurt, Johannes; Kalman, Jonathan M.; Tanel, Ronn E.; et al.
Abstract : Background: Nodofascicular and nodoventricular (NFV) accessory pathways connect the atrioventricular node and the Purkinje system or ventricular myocardium, respectively. Concealed NFV pathways participate as the retrograde limb of supraventricular tachycardia (SVT). Manifest NFV pathways can comprise the anterograde limb of wide-complex SVT but are quite rare. The purpose of this report is to highlight the electrophysiological properties and sites of ablation for manifest NFV pathways. Methods: Eight patients underwent electrophysiology studies for wide-complex tachycardia (3), for narrow-complex tachycardia (1), and preexcitation (4). Results: NFV was an integral part of the SVT circuit in 3 patients. Cases 1 to 2 were wide-complex tachycardia because of manifest NFV SVT. Case 3 was a bidirectional NFV that conducted retrograde during concealed NFV SVT and anterograde causing preexcitation during atrial pacing. NFV was a bystander during atrioventricular node re-entrant tachycardia, atrial fibrillation, atrial flutter, and orthodromic atrioventricular re-entrant tachycardia in 4 cases and caused only preexcitation in 1. Successful NFV ablation was achieved empirically in the slow pathway region in 1 case. In 5 cases, the ventricular insertion was mapped to the slow pathway region (2 cases) or septal right ventricle (3 cases). The NFV was not mapped in cases 5 and 7 because of its bystander role. QRS morphology of preexcitation predicted the right ventricle insertion sites in 4 of the 5 cases in which it was mapped. During follow-up, 1 patient noted recurrent palpitations but no documented SVT. Conclusions: Manifest NFV may be critical for wide-complex tachycardia/manifest NFV SVT, act as the retrograde limb for narrow-complex tachycardia/concealed NFV SVT, or cause bystander preexcitation. Ablation should initially target the slow pathway region, with mapping of the right ventricle insertion site if slow pathway ablation is not successful. The QRS morphology of maximal preexcitation may be helpful in predicting successful right ventricle ablation site. Abstract : Supplemental Digital Content is available in the text.